Strengthening Farmer Group Capacity through Integrated Farming Development in Purworejo Village, Blitar Regency - Siti Azizah; Dede Aprylasari; Widi Nugroho; Anif Mukaromah Wati; Ahmad Ridwan; Mona Ghaly; Neneng Kusumaningrum (LOSARI DIGITAL, 2026)
This community service activity aimed to identify the potentials and challenges of the agricultural and livestock sectors and to formulate integrated farming development strategies in Purworejo Village, Wates District, Blitar Regency. A participatory community empowerment approach was applied through field observations, Focus Group Discussions (FGD), participatory interviews, and qualitative descriptive analysis involving 42 members of the Mbening Makmur Farmer Group. Purworejo Village has approximately 39.79 ha of actively cultivated agricultural land with leading commodities including corn, chili, shallots, cabbage, cattle, goats, and laying hens. The results showed that approximately 76% of participants gained new knowledge regarding organic waste utilization and integrated farming systems after the extension activities, while 68% expressed interest in implementing fermented feed technology using agricultural waste. Several major constraints identified included pest attacks, livestock diseases, low technology adoption, limited market access, and suboptimal waste management. Agricultural and livestock waste were identified as having strong potential to be utilized as fermented feed and organic fertilizer within an integrated farming system. Recommended strategies include training in waste processing, strengthening farmer group capacity, continuous mentoring programs, and improving product marketing assistance to support productivity, farming efficiency, and environmental sustainability.